Rationally-designed self-shaped ceramics through heterogeneous green body compositions. Issue 11 (19th August 2022) - Ding, Zizhen; Zreiqat, Hala; Mirkhalaf, Mohammad
Abstract : A material- and scale-independent ceramic self-shaping technique using heterogeneous green body compositions resulted in a rich set of shape changes. A model predicted shape change precisely and can serve as a design tool for future developments. Abstract : Forming ceramics into rationally-designed and complex shapes without compromising their mechanical properties is a major challenge. Here, we demonstrate self-shaping of ceramics through sequential stereolithographic printing of ceramic resins into components with a heterogeneous concentration of ceramic particles, resulting in well-defined anisotropic shrinkage and, consequently, shape changes during sintering. The method is versatile and scalable and results in well-controlled shape changes in ceramics through bending, folding, twisting, and combinations of these mechanisms. The density measurements and mechanical tests show that the stresses resulting from the self-shaping mechanisms do not significantly affect the physical and mechanical properties of the ceramics. Together with the experiments, we developed a material- and scale-independent mechanical model based on linear elasticity that predicted shape changes accurately. The model can serve as a design tool to guide the selection of particle concentrations to realize the desired shapes in a broad range of ceramics.